Rozmieszczenie i zatrudnienie absolwentów Akademii Ekonomicznej w Poznaniu w latach 1929-1972 - Chromińska, Maria (Wydział Prawa i Administracji UAM, 1976)
In 1976, the Academy of Economics celebrated its 50 th anniversary. On this occasion the Author Member of the Potator Seminar in Demography worked up the doctor dissertation on "The Effects of Education of Economists at the Accademy of Economies in 1926 - 1975". The (presented article is a fragment of the dissertation. The Author found addresse and sent inquizy questionaire to 8250 of 9725 graduates; of which 2932 respondents sent bach the filled questioinaire. The distribution of respondents by sex, aigle and social origin, by completed faculty and specialization is very near to that of the all graduates. The respondents have been scattered in all the new voivodships of Poland and employed in all divions of the Polish economy. Most of them develop their economic and professional activity in industry and commerce, in sciences and education. Many of the respondents have occupied the highest and the exposed position in the state and regional governments as well as at schods of university level and in the state enterprises.
Employment and Regional Distribution of the Graduates of the Academy of Economics in Poznań, in 1928-1972